Refrigerated amniotic membrane maintains its therapeutic qualities for 48 hours - Stelling-Férez, J.; Puente-Cuadrado, J. M.; Álvarez-Yepes, V.; Alcaraz, M.; Tristante, E.; Hernández-Mármol, I.; Mompeán-Egea, I.; García-Hernández, A. M.; Nicolás, F. J. (Frontiers in Bioengineering and Biotechnology, 2024)
During wound healing, the migration of keratinocytes is critical for wound closure. The application of amniotic membrane (AM) on wounds with challenging contexts (e.g., chronification, diabetic foot ulcer) has proven very successful. However, the use of AM for clinical practice has several restraints when applied to patients, the most important one, preserving AM's therapeutic properties between its thawing and application onto the patient's wound. Moreover, AM collection and processing requires a cleanroom, together with specialized staff and equipment, facilities that are not usually available in many hospitals and healthcare units. In this publication we kept previously cryopreserved AM at different temperatures (37 ºC, 20 ºC, 4 ºC), in different media (DMEM High Glucose, saline solution with or without human albumin) and for long incubation time periods after thawing (24 h, 48 h). HaCaT keratinocytes and TGF-β1-chronified HaCaT keratinocytes were used to measure several parameters related to wound healing: migration, cell cycle arrest rescue, and the expression of key genes and migration-related proteins. Our findings indicate that AM kept in physiological saline solution at 4 °C for 24 h or 48 h performed excellently in promoting HaCaT cell migration compared to AM that had been immediately thawed (0 h). Indeed, key proteins, ERK and c-Jun, were induced by AM at 4 ºC in saline solution. Similarly, cell proliferation and different genes related to survival, inflammation and senescence had, in all cases, the same response as to standard AM. These data suggest that the handling method in saline solution at 4 °C does not interfere with AM therapeutic properties.